2015
DOI: 10.1039/c4an02187h
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale pillar arrays for separations

Abstract: The work presented herein evaluates silicon nano-pillar arrays for use in planar chromatography. Electron beam lithography and metal thermal dewetting protocols were used to create nano-thin layer chromatography platforms. With these fabrication methods we are able to reduce the size of the characteristic features in a separation medium below that used in ultra-thin layer chromatography; i.e. pillar heights are 1-2 μm and pillar diameters are typically in the 200-400 nm range. In addition to the intrinsic nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…Silicon wafers with 1-3 μm diameter, 15-20 μm tall cylindrical pillars in a 1 cm × 3 cm array (spacing of 2-6 μm between pillars), modified with a C18 reversed phase coating, were tested for efficiency as thin-layer chromatography (TLC) plates [64,65]. Compared to commercial TLC plates, chromatographic efficiency was ~3-5 times better for the pillar array [64].…”
Section: Discussionmentioning
confidence: 99%
“…Silicon wafers with 1-3 μm diameter, 15-20 μm tall cylindrical pillars in a 1 cm × 3 cm array (spacing of 2-6 μm between pillars), modified with a C18 reversed phase coating, were tested for efficiency as thin-layer chromatography (TLC) plates [64,65]. Compared to commercial TLC plates, chromatographic efficiency was ~3-5 times better for the pillar array [64].…”
Section: Discussionmentioning
confidence: 99%
“…Some nanomaterials for UTLC have been made by combining the methods of GLAD and ALD . It was found in one report by Brett and co‐workers that the surface area of the resulting media depended on the ALD coating thickness of aluminum oxide, as examined through its effect on the separation of lipophilic dyes .…”
Section: Nanomaterials In Planar Liquid Chromatographymentioning
confidence: 99%
“…using GLAD to deposit microstructures of silica as slanted columnar thin films on glass, followed by the use of ALD to coat these structures with alumina. These materials have been used in combination with anisotropic contrast optical microscopy to simultaneously separate and detect lipophilic dyes on small UTLC plates .…”
Section: Nanomaterials In Planar Liquid Chromatographymentioning
confidence: 99%
“…It was demonstrated that plate height (H) is improved due to the lack of eddy diffusion, less resistance to mass transfer in the mobile phase with smaller pillar diameters and interpillar gaps, as well as less molecular diffusion band broadening due to greater permeability. More recently, we have reduced the scale of the planar chromatographic platforms to nanodimensions using electron beam lithography and metal dewetting (DW) fabrication methods . With both the UTLC pillar arrays and the nanoscale cases the flow is considerably faster than for traditional TLC, however efficiency is still limited during most of the development by molecular diffusion .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, we have reduced the scale of the planar chromatographic platforms to nanodimensions using electron beam lithography and metal dewetting (DW) fabrication methods . With both the UTLC pillar arrays and the nanoscale cases the flow is considerably faster than for traditional TLC, however efficiency is still limited during most of the development by molecular diffusion . Hence, we explore the use of centrifugal force (CF), a forced‐flow technique, to augment flow in reduced‐dimension planar chromatography.…”
Section: Introductionmentioning
confidence: 99%